THE IMPLEMENTATION OF LAW NUMBER 56 LAW IN LIEU OF LAW NUMBER 1960 CONCERNING THE STIPULATION OF AGRICULTURAL LAND AREA IN THE REGENCY OF WEST LOMBOK - Fitria, Bq. Mahyuniati (Jurnal IUS, 2013)
One of the purpose of landreform is to do a fair share of the peopleâs livelihood of farmers in the form of land , with the intention that there is a fair distribution of outcomes is to overhaul the structure of the land in order to realize social justice . To achieve this, it made landreform programs, among others, restrictions on the maximum area of land dominance and determination of minimum area of agricultural land ownership , and prohibition on acts that lead to breakdown of ownership of agricultural land into pieces that are too small . Then the program is poured in a legislation that is through Act No.56 PRPÂ 1960 on the establishment of the agricultural land area . However , for the region of western Lombok , based on observations of this law is still very difficult to apply .Keywords : Landreform , Land Area Restrictions